Regulating the Sacred: Religious Environmental Degradation and Legal Reform in Nigeria - Ganiyu Yahaya; Adefisayo Oyedeji; Adeola Olufunke Kehinde (Fakultas Syariah UIN Sultan Aji Muhamamd Idris Samarinda, 2026)
Apart from Nigeria's worrisome economic situation, environmental degradation is also an alarming issue across the country. Religious institutions in Nigeria play a pivotal yet underexplored role, from deforestation for church and mosque constructions to indiscriminate waste disposal by large congregations. This paper examines the role of religious institutions in environmental degradation in Nigeria and explores how religious practices align with environmental sustainability. While religion plays a dominant role in Nigerian society, religious institutions contribute to environmental challenges through large-scale land acquisition, deforestation, indiscriminate waste disposal and management, and noise pollution. Using the doctrinal method of legal research, this paper further examines relevant constitutional and statutory provisions, analyses judicial authorities, and draws comparative lessons from other jurisdictions, including Saudi Arabia and India. The paper concludes that the impact of religious institutions in Nigeria cannot be overemphasized in ensuring a healthy environment. It recommended integrating eco-theology into religious teachings and called for stronger enforcement of environmental laws in Nigeria.